(untitled) (Research, Society and Development, 2024)
Obesity is a multifactorial condition associated with health risks, requiring effective and safe therapeutic approaches for weight control. The objective of the present study is to present a review of scientific evidence on the advantages of semaglutide in the treatment of obesity, to raise awareness among readers, and to expand knowledge on the topic. An integrative literature review was conducted using Google Scholar, MEDLINE/PUBMED, and SciELO, considering articles published between 2014 and 2024. Studies on the efficacy, safety, and role of healthcare professionals in the use of semaglutide for obese or overweight patients were included. Semaglutide, a GLP-1 receptor agonist, demonstrated an average body weight reduction of 10% to 15% across multiple studies, acting by decreasing appetite and increasing satiety. Patients treated with semaglutide showed better long-term weight control when compared to non-pharmacological interventions alone. Semaglutide proved to be an effective and safe pharmacological option for weight loss, especially for patients struggling with weight management through lifestyle changes alone. However, the treatment requires continuous monitoring and behavioral changes to maintain results. Additional studies are recommended to explore its efficacy in different population subgroups and assess long-term effects.